Law, state and the politics of catastrophes: a critical perspective on epiphanies of injustice and the need for protection - Nitrato Izzo, Valerio (Oñati Socio-Legal Series, 2013)
While the phenomenon of catastrophes is emerging as a growing threat that humanity should face in the next years, legal studies have disregarded the issue for a long time. Recent extreme events have motivated a new attention towards the legal dimension as part of the context in which disasters take place. Catastrophes are a powerful breakdown of our normative world. Paradigms of regulation in this field have usually been identified in terms of prevention, anticipation and amelioration, theoretical schemes that can be applied to various branches of the law. Nevertheless, this is only a part of the challenge that the legal study of extreme events must face. They should in fact include into these abstract schemes the factors of inequality that contribute to producing higher rates of vulnerability. In this paper I propose to conceive catastrophes as legal epiphanies, through which it is possible to evaluate the effectiveness, the efficiency and the sustainability of regulatory choices.